Isolation and characterization of Wharton's jelly-derived multipotent mesenchymal stromal cells obtained from bovine umbilical cord and maintained in a defined serum-free three-dimensional system - Cardoso, Tereza C. [UNESP]; Ferrari, Heitor F. [UNESP]; Garcia, Andrea F. [UNESP]; Novais, Juliana B. [UNESP]; Silva-Frade, Camila [UNESP]; Ferrarezi, Marina C. [UNESP]; Andrade, Alexandre Lima de [UNESP]; Gameiro, Roberto [UNESP] (Biomed Central Ltd., 2012)
Background: The possibility for isolating bovine mesenchymal multipotent cells (MSCs) from fetal adnexa is an interesting prospect because of the potential for these cells to be used for biotechnological applications. Bone marrow and adipose tissue are the most common sources of MSCs derived from adult animals. However, little knowledge exists about the characteristics of these progenitors cells in the bovine species. Traditionally most cell cultures are developed in two dimensional (2D) environments. In mammalian tissue, cells connect not only to each other, but also support structures called the extracellular matrix (ECM). The three-dimensional (3D) cultures may play a potential role in cell biotechnology, especially in tissue therapy. In this study, bovine-derived umbilical cord Wharton's jelly (UC-WJ) cells were isolated, characterized and maintained under 3D-free serum condition as an alternative of stem cell source for future cell banking.Results: Bovine-derived UC-WJ cells, collected individually from 5 different umbilical cords sources, were successfully cultured under serum-free conditions and were capable to support 60 consecutive passages using commercial Stemline (R) mesenchymal stem cells expansion medium. Moreover, the UC-WJ cells were differentiated into osteocytes, chondrocytes, adipocytes and neural-like cells and cultured separately. Additionally, the genes that are considered important embryonic, POU5F1 and ITSN1, and mesenchymal cell markers, CD105(+), CD29(+), CD73(+) and CD90(+) in MSCs were also expressed in five bovine-derived UC-WJ cultures. Morphology of proliferating cells typically appeared fibroblast-like spindle shape presenting the same viability and number. These characteristics were not affected during passages. There were 60 chromosomes at the metaphase, with acrocentric morphology and intense telomerase activity. Moreover, the proliferative capacity of T cells in response to a mitogen stimulus was suppressed when bovine-derived UC-WJ cells was included in the culture which demonstrated the immunossupression profile typically observed among isolated mesenchymal cells from other species. After classified the UC-WJ cells as mesenchymal stromal phenotype the in vitro 3D cultures was performed using the AlgiMatrix (R) protocol. Based on the size of spheroids (283,07 mu m +/- 43,10 mu m) we found that three weeks of culture was the best period to growth the UC-WJ cells on 3D dimension. The initial cell density was measured and the best value was 1.5 x 10(6) cells/well.Conclusions: We described for the first time the isolation and characterization of UC-WJ cells in a serum-free condition and maintenance of primitive mesenchymal phenotype. The culture was stable under 60 consecutive passages with no genetic abnormalities and proliferating ratios. Taken together all results, it was possible to demonstrate an easy way to isolate and culture of bovine-derived UC-WJ cells under 2D and 3D serum-free condition, from fetal adnexa with a great potential in cell therapy and biotechnology.
Keywords: Wharton's jelly stem cells; Mesenchymal stromal cells; Differentiation; Immunomodulation